The Impact of Video Game Addiction on Depression, Anxiety, and Stress among Thai Adolescents, Mediated by Self-Regulation and Social Support - Rujataronjai, Warin; Varma, Parvathy (Scholar: Human Sciences, 2017)
The primary purpose of this study was to examine the direct and indirect influences of video game addiction on Thai adolescents’ levels of depression, anxiety, and stress, being mediated by self-regulation and social support. A total of 200 Thai adolescents (aged between 18 and 20 years) participated in this study by filling in a self-administered survey questionnaire designed to measure the study’s primary variables (video game addiction, depression, anxiety, stress, self-regulation, and social support). Results from the path analysis showed that the respondents’ level of video game addiction directly influenced the levels of depression, anxiety, and stress such that the higher the level of video game addiction, the higher is their level of depression, anxiety, and stress. Video game addiction has indirect influences on the levels of depression, anxiety, and stress when mediated by self-regulation. However, video game addiction has no indirect influence on anxiety and stress when mediated by social support. Nonetheless, video game addiction was found to have a positive influence on social support, such that the higher the level of addiction, the higher is the level of social support. Among the three dependent variables of depression, anxiety, and stress, it was found that only depression decreases in level when the mediator social support is increased, even when the level of video game addiction is high. The study’s conclusions, implications, and avenues for future research are discussed.